Proteasomes generate spliced epitopes by two different mechanisms and as efficiently as non-spliced epitopes - Ebstein, F; Textoris-Taube, K; Keller, C; Golnik, R; Vigneron, N; Van den Eynde, B; Schuler-Thurner, B; Schadendorf, D; Lorenz, F; Uckert, W; Urban, S; Lehmann, A; et al. (Nature Publishing Group, 2016)
Proteasome-catalyzed peptide splicing represents an additional catalytic activity of proteasomes contributing to the pool of MHC-class I-presented epitopes. We here biochemically and functionally characterized a new melanoma gp100 derived spliced epitope. We demonstrate that the gp100(mel)47-52/40-42 antigenic peptide is generated in vitro and in cellulo by a not yet described proteasomal condensation reaction. gp100(mel)47-52/40-42 generation is enhanced in the presence of the β5i/LMP7 proteasome-subunit and elicits a peptide-specific CD8(+) T cell response. Importantly, we demonstrate that different gp100(mel)-derived spliced epitopes are generated and presented to CD8(+) T cells with efficacies comparable to non-spliced canonical tumor epitopes and that gp100(mel)-derived spliced epitopes trigger activation of CD8(+) T cells found in peripheral blood of half of the melanoma patients tested. Our data suggest that both transpeptidation and condensation reactions contribute to the frequent generation of spliced epitopes also in vivo and that their immune relevance may be comparable to non-spliced epitopes.